Rhetoric of Repairs: Pathos Analysis of Joe Biden’s Victory Speech (The Spectrum, 2024)
This paper aims to explore pathos, the prominent emotional appeal, in Joe Biden’s presidential victory speech delivered on 7 November 2020 at Wilmington in the United States of America. The speech was delivered upon the conclusion of the presidential race between Donald Trump and Joe Biden, wherein Biden led the election with 306 electoral votes against Trump’s 232. The paper is informed by three objectives: how Biden’s speech seeks to arouse certain emotions in the audience, what emotions in the audience are triggered, and how those emotions assist Biden in successfully delivering his intent of repair and reconciliation by persuading his audience, the American people. To fulfill these objectives, employing the method of a rhetorical analysis, the paper explicates the speech investigating how the lexical choices in the victory speech appeal to specific feelings and emotions of the audience. The analysis concludes that Biden, the orator, warrants reconstruction and reconciliation by appealing to seven dominant emotions: confidence, trust, optimism, (in)gratitude, empathy, camaraderie, and American pride. Hence, the paper demonstrates the fundamentals of doing a rhetorical analysis and further motivates some aspirants seeking a career in script writing and oratory.